Hubungan Pengetahuan dan Sikap Dengan Perilaku Ibu Terhadap Pencegahan COVID-19 Pada Masa Kanak-Kanak - Haninda Ruwaidah; Karina Nur Ramadhanintyas; Riska Ratnawati (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
In Indonesia, the number of positive cases in children aged 6-18 years is 9.3% while in Magetan Regency, the number of positive cases in children aged 6-18 years as of January 17, 2021 is 19 cases. The purpose of this study was to analyze the relationship between knowledge and attitudes with COVID-19 prevention behavior in childhood. This type of research uses aapproach cross sectional. The target of this study is mothers who have children aged 6-12 years, with a total population of 143 populations and a sample of 105 populations, and using simple random sampling technique. The data analysis technique used bivariate analysis ofstatistical test chi-square. The results of thetest chi-square showed that there was a relationship between knowledge (p < 0.002) and attitude (p < 0.001) with COVID-19 prevention behavior in childhood. Mother's knowledge and attitudes are related to COVID-19 prevention behavior, because in childhood they still need supervision from parents, especially mothers.  Suggestions for further research to make more applicative approaches to the community through leaflets or booklets for interventions on COVID-19 prevention behavior.Keywords: Attitude, COVID-19, Knowledge